Analisis Kumpulan Puisi “Perahu Kertas Karya Sapardi Djoko Damono Menggunakan Pendekatan Stilistika yang Berorientasi pada Pemajasan - Ayi Herisna; Irpan Mulana; Desti Kusmayanti (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to analyze stylistic elements in a collection of poems using a stylistic approach with content analysis methods and a library research design. The data, consisting of words and phrases from 19 poems, were categorized into figures of speech, structural manipulation, and imagery. Data collection techniques included reading, observing, and note-taking. The analysis revealed a rich variety of language styles, with 82 instances of figurative language, 65 structural manipulations, and 98 uses of imagery that enhance the meaning and rhythm of the poems. These findings were implemented into an e-learning poetry module, validated by two experts and applied at SMA Negeri 1 Tanjungsiang. Based on questionnaires completed by 35 students, 96.9% of responses indicated that the module was clear, engaging, and supportive of independent learning.